Mutual Coupling Reduction of a Circularly Polarized MIMO Antenna Using Parasitic Elements and DGS for V2X Communications - Md. Abu Sufian; Niamat Hussain; Anees Abbas; Jaemin Lee; Seong Gyoon Park; Nam Kim (IEEE Access)
In this article, a 4-port circularly polarized (CP) multiple-input multiple-output (MIMO) antenna at 5.9 GHz is presented for the vehicle to everything (V2X) communications. A novel hybrid decoupling structure consisting of circular ring parasites and defected ground structure (DGS) is used to reduce the mutual coupling between the MIMO elements. The circular ring parasites are incorporated between the antennas to reduce the mutual coupling between perpendicular antennas. Whereas, the DGS significantly reduces the mutual coupling between adjacent antennas. These circular ring parasites and DGS affect the electromagnetic field distribution and consequently reduce the mutual coupling. The effectiveness of the decoupling structure is explained through transmission coefficient and surface current distribution. The simulated and measured results show that the proposed MIMO antenna provides overlapping $\text{S}_{\mathrm {11 {}}}$ (−10 dB) and axial ratio (3-dB) bandwidth of 2.04% (5.82 – 5.94 GHz) with a peak gain of 7.68 dBic. Moreover, the fabricated MIMO antenna offers excellent diversity performance, isolation between antenna elements is very high (>34dB), envelope correlation coefficient (ECC) is lower than 0.001, and diversity gain is 9.99 dB, very close to the ideal value of 10 dB. Furthermore, the link budget for the proposed MIMO system is calculated to check the suitability for V2X communications which shows that the antenna can communicate between them over a distance of 1.5 kilometers with a 21 dBm of transmit power. Owing to these qualities, the proposed MIMO antenna can be an excellent choice for V2X MIMO communications.